HUBUNGAN BEBAN KERJA DENGAN KEJADIAN ABORTUS SPONTAN PADA PEREMPUAN YANG BEKERJA DI SENTRA PERTANIAN DI KABUPATEN LOMBOK TIMUR - , Misroh Mulianingsih, dr. Ova Emilia, M.M.Ed, SpOG(K), Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Maternal Mortality Rate (MMR) according to the 2007 Indonesia Demographic Health Survey (IDHS) is still 228/100.000 live births, 90% caused by hemorrhage, toxemia gravidarum, infection, and spontaneous abortion. The number of maternal deaths caused by bleeding in West Nusa Tenggara (NTB) Province in 2008 was 44.2% and in East Lombok District until July of 2009 the number was 113/100.000 live births. Objective: To determine the determinant factors likely to cause spontaneous abortion in the agricultural center of East Lombok District. Methods: This was an observational study with a quantitative approach supported by an in-depth interview guide. The collection of secondary data was obtained from inpatient registers in MCH poly, a cohort of pregnant women. Primary data collection was conducted through interviews. The study subjects were women who had experienced spontaneous abortion at gestational age <20 weeks working in the agricultural center in East Lombok. Sampling technique was with simple random sampling. The stages of data analysis included univariable, bivariable and multivariable analysis. Results: Based on the results of bivariable analysis, there was a significant association between workload (p value = 0.0006), age (p-value = 0.032), nutritional status (p-value = 0.022), and spacing of pregnancy (pvalue = 0.009) and the incidence of spontaneous abortion. There was no significant association between parity (p-value = 0.009) and history of spontaneous abortion (p-value = 0.67) and the incidence of spontaneous abortion. Based on multivariable analysis, the risk of an inappropriate workload during pregnancy (OR = 3.53